1998
DOI: 10.1055/s-2007-979309
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Psychotomimetic or Impairing Effects on Psychomotor Performance of Acamprosate

Abstract: Cognitive impairments during psychotic episodes are assumed to be caused not only by one single putative classical neurotransmitter dysfunction but also to be due to an impaired equilibrium of the interaction between different neurobiological generators of cognitive processes. Here, the perceptual abnormalities induced by psychotogenic agents play a major role as tools for understanding model psychoses. The recently discovered cannabinoid receptor system with its endogenous ligand anandamide can be regarded as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 3 publications
(5 reference statements)
2
5
0
Order By: Relevance
“…Studies in healthy subjects have shown that acamprosate is devoid of any sedative effects per se (Schneider et al, 1998); thus, the present results bring support to our working hypothesis that acamprosate could improve postwithdrawal sleep disturbances by lowering the withdrawal-associated neural hyperexcitability and, therefore, CNS hyperarousal. In accordance with this, daytime assessments by electroencephalography and magnetoencephalography also indicate that acamprosate attenuates electrophysiological signs of CNS hyperexcitability during alcohol withdrawal (Boeijinga et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…Studies in healthy subjects have shown that acamprosate is devoid of any sedative effects per se (Schneider et al, 1998); thus, the present results bring support to our working hypothesis that acamprosate could improve postwithdrawal sleep disturbances by lowering the withdrawal-associated neural hyperexcitability and, therefore, CNS hyperarousal. In accordance with this, daytime assessments by electroencephalography and magnetoencephalography also indicate that acamprosate attenuates electrophysiological signs of CNS hyperexcitability during alcohol withdrawal (Boeijinga et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…Because of a broad mechanism of action, further investigation with acamprosate may uncover multiple receptor systems that contribute to relapse. Regardless of its many potential neurochemical targets, acamprosate lacks abuse potential and presents a mild side effect profile in humans (Grant and Woolverton 1989;Le Magnen et al 1987;Mcgeehan and Olive 2003;Naassila et al 1998;Nalpas et al 1990;Schneider et al 1998;Spanagel et al 1996). While further preclinical studies are needed to determine if acamprosate attenuates cocaine relapse induced by other stimuli such as stress, our data suggest that acamprosate may be a novel pharmacological therapeutic particularly useful in reducing the incidence of relapse in cocaine addiction.…”
Section: Discussionmentioning
confidence: 77%
“…13 Acamprosate lessens sleep disturbances in a dependent population, 14 even while it has no effect on sleep in healthy participants. 15 Results with gabapentin are mixed, with some reporting an improvement in disturbed sleep, 13 and others reporting no effect on sleep. 16 Normalization of sleep during alcohol withdrawal is important because these withdrawal-associated sleep disturbances may precipitate or contribute to relapse.…”
Section: Introductionmentioning
confidence: 99%
“…11,13,17,18 Most medications for treating alcohol dependence also have an effect on sleep. [12][13][14][15] Thus, it is important to determine any effect of a candidate medication for alcohol dependence, such as kudzu root extract, on sleep quality and quantity. If a precipitating factor of relapse is the disturbed sleep associated with alcohol withdrawal and a medication used to treat alcohol withdrawal further disrupts sleep, then patients could experience a ''double whammy'' effect from the medication, further challenging their attempt to quit drinking.…”
mentioning
confidence: 99%